2022
DOI: 10.1002/hec.4503
|View full text |Cite
|
Sign up to set email alerts
|

An examination of machine learning to map non‐preference based patient reported outcome measures to health state utility values

Abstract: Non‐preference‐based patient‐reported outcome measures (PROMs) are popular in health outcomes research. These measures, however, cannot be used to estimate health state utilities, limiting their usefulness for economic evaluations. Mapping PROMs to a multi‐attribute utility instrument is one solution. While mapping is commonly conducted using econometric techniques, failing to specify the complex interactions between variables may lead to inaccurate prediction of utilities, resulting in inaccurate estimates of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 113 publications
(108 reference statements)
1
7
0
Order By: Relevance
“…It could thus be more rigorous to administer a relevant questionnaire, like PROMIS Global Health-10 questionnaire. 32 Despite excluding other medical conditions that may impact QoL and decision regret before the investigation, the participants might have undetected diseases, which would influence the conclusion. This is our study's weakness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It could thus be more rigorous to administer a relevant questionnaire, like PROMIS Global Health-10 questionnaire. 32 Despite excluding other medical conditions that may impact QoL and decision regret before the investigation, the participants might have undetected diseases, which would influence the conclusion. This is our study's weakness.…”
Section: Discussionmentioning
confidence: 99%
“…Although the main objective of this study is to utilise the ThyPRO‐39 and DRS scales to evaluate patients with thyroid‐related diseases’ quality of life and decision regret, it should be noted that other factors such as social environment and psychological health will potentially affect the outcomes. It could thus be more rigorous to administer a relevant questionnaire, like PROMIS Global Health‐10 questionnaire 32 . Despite excluding other medical conditions that may impact QoL and decision regret before the investigation, the participants might have undetected diseases, which would influence the conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Employing machine learning techniques for mapping is still uncommon [ 29 ]. However, some mapping studies have taken this path in recent years [ 41 , 54 , 55 ]. Because the core strength of machine learning is prediction, mapping studies appear to be a suitable application field for it.…”
Section: Discussionmentioning
confidence: 99%
“…For model selection and estimation, only the model subset was used. We selected one final model for each covariate scenario based on tenfold cross-validation, which has become increasingly popular for mapping studies in recent years (e.g., [ 37 41 ]). We thus randomly split the sample into 10 folds, i.e., equally sized parts of the data set.…”
Section: Methodsmentioning
confidence: 99%
“…They found that the machine learning technique performed similarly to the traditional econometric methods in three out of the four countries of their sample. Another study by Aghdaee et al [ 22 ] also found that machine learning (e.g., Lasso regression) performed marginally better if not combined with other traditional econometric methods ( n = 2015). Despite these previous findings, machine learning still has the advantage of determining the nature of the relationships without researchers trying to guess the possible combinations between them or imposing their bias on the results by selecting their preferred functional form.…”
Section: Introductionmentioning
confidence: 98%